Skala Sikap: Konsep, Jenis, dan Implikasi dalam Pendidikan - Ridho, Ahmad Rosyid; Nuryahya, Ikhsan (TSAQOFAH, 2026)
Attitude measurement has been widely examined in social and educational studies; however, the challenges of transforming subjective viewpoints into objective numerical data and determining appropriate measurement tools still require in-depth methodological scrutiny. This study aims to examine various types of attitude scales and underscore the urgency of validity and reliability testing in the design of research instruments. The research employed a qualitative method based on library research, collecting data from secondary sources in the form of books and scholarly journals through systematic literature searches, which were subsequently analyzed using content analysis techniques. The findings identify four main categories of scales for measuring affective aspects, namely the Likert scale, Guttman scale, semantic differential, and Thurstone scale, each of which has distinct characteristics in producing nominal, ordinal, and interval-level data and in detecting the intensity of respondents’ attitudes. These findings enrich the research methodology literature by clarifying the function and position of each scale in the selection of instruments aligned with research purposes and design. It is concluded that the accuracy of attitude measurement is strongly influenced by the appropriateness of scale selection in relation to the characteristics of the construct and data, as well as the rigor of validity and reliability testing; therefore, researchers are recommended to select scales according to the desired level of precision and to consider the use of advanced analytical models such as the Rasch model for item calibration purposes.